A study of perceived competencies among trainers in TNB Training Institute - ILSAS, Bangi / Sarawani Shafie - Shafie, Sarawani (Faculty of Business and Management, 2006)
Are the trainers having enough competencies skills for them to train the trainees? The purpose of this study was to investigate the perceived attainments made by the trainers. Also this study investigates the actual attainments made by the trainees for their trainers. And also want to know if there is a gap between those two. This study also investigates the comments and suggestions on how to improve the quality of the trainers. The results of this research show that there is a negative gap between the actual attainments and the perceived attainments. The negative gap means that the perceived attainments made by the trainers are higher than the actual attainments made by the trainees for their trainers. This shows that the trainers are not good enough in terms of the trainers' competencies.